Designing an environmental training program from an inter-transversal approach - Cardona Fuentes , José Alberto; Vera Toledo , Janny M. (Transformación, 2024)
An environmental educational program is devised based on the notion of inter-transversability —as described in a prior research and considering the shortcomings of teachers of sciences training process—. The program is aimed at environmental protection sustainable development; it is characterized by its inter-transversal approach, its theoretical and practical character, and its contribution to teachers’ educational and environmental professional performance. The program has been in use in 12 classes and assessed by means consulting experts on the topic.